(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
Because of the frequent use of triclabendazole TCBZ by farmers and the recent reports of Fasciola hepatica resistance to this drug in herds and flocks from Neuquén, we carried out this study with the aim to evaluate the efficacy of TCBZ as fasciolicide in goats under a transhumance system from northern of Neuquén, Argentina. A fecal egg count reduction test (FECRT) was performed on Creale Neuquino goats naturally parasitized with F. hepatica. Twenty goats were divided into two groups: A control group (n: 10) which was left untreated, and a treatment group (n: 10) that was dosed orally with TCBZ 10% (Biofasiolex T10-Biogénesis Bagó ®). On Day 0 and Day 21 post-treatment, fecal samples were taken and analyzed by coproscopical examination. According to the FECRT, drug efficacy was 100 % and confirms that TCBZ maintains its efficacy against F. hepatica on goats. The usefulness of the FECRT in these zones under transhumance livestock production is discussed.